Emergent Thrombectomy in a Neonate with an Upper Extremity Arterial Thrombus - Ulrich, Timothy J. B.; Ellsworth, Marc A.; Lang, Tara R. (American Journal of Perinatology Reports, 2014)
Case This case report is of a 39 4/7weeks infant who presented at the time of birth with an immobile, cyanotic right upper extremity consistent with ischemia but without evidence of gangrene. Doppler examination identified pulses in the axillary but not the brachial or radial arteries. Extremity arterial ultrasound confirmed the diagnosis of an arterial thrombosis extending from the right axillary artery to the brachial artery bifurcation. An emergent balloon thrombectomy was performed successfully with immediate return of blood flow. Intraoperative ultrasound demonstrated patent axillary and brachial arteries with forward flow. A retroperitoneal ultrasound and limited hypercoagulable workup failed to identify a source of the arterial thrombus. The infant had normal return of function without residual limb effects.Conclusion Emergent balloon thrombectomy should be heavily considered in neonates with an extremity arterial thrombosis of undeterminable duration both for limb salvage, preserve function, and to prevent long-term growth discordance.
Keywords: neonate; arterial thrombus; thrombectomy; ischemia